Direct Growth of MoO2/Reduced Graphene Oxide Hollow Sphere Composites as Advanced Anode Materials for Potassium‐Ion Batteries. Issue 4 (29th January 2019) - Liu, Cailing; Luo, Shaohua; Huang, Hongbo; Zhai, Yuchun; Wang, Zhaowen
Abstract: Hollow MoO2 /reduced graphene oxide (MoO2 /rGO) sub‐microsphere composites have been fabricated through a simple hydrothermal approach followed by a heat treatment process. When employed as an anode material for potassium‐ion batteries, the as‐synthesized MoO2 /rGO composite can deliver an initial charge specific capacity of 367.2 mAh g −1 at 50 mA g −1, and its reversible capacity is 218.9 mAh g −1 after 200 cycles. Even when cycled at 500 mA g −1, a high charge specific capacity of 104.2 mAh g −1 is achieved after 500 cycles. The excellent cycling capability and rate performance may be ascribed to the synergistic effects of the reduced graphene oxide and the hollow MoO2 spheres, which can increase the electrical conductivity of the composite, as well as resisting the strain arising from the repeated discharge–charge processes. These results indicate that the MoO2 /rGO hollow sphere composites are promising negative electrode materials for potassium‐ion batteries. Abstract : Hollow can you go? Hollow MoO2 /reduced graphene oxide (MoO2 /rGO) sub‐microsphere composites have been fabricated through a simple hydrothermal approach followed by heat treatment. When employed as an anode material for potassium‐ion batteries, the as‐synthesized MoO2 /rGO composite deliver an initial charge specific capacity of 367.2 mAh g −1 at 50 mA g −1, and its reversible capacity is 218.9 mAh g −1 after 200 cycles.